2021
DOI: 10.3390/sym13020311
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Periodic Transient Pressure Fluctuation in a Centrifugal Pump Impeller at Low Flow Rate

Abstract: This paper presents a large eddy simulation of a centrifugal pump impeller during a transient condition. The flow rate is sinusoidal and oscillates between 0.25Qd (Qd indicates design load) and 0.75Qd when the rotating speed is maintained. Research shows that in one period, the inlet flow rate will twice reach 0.5Qd, and among the impeller of one moment is a stall state, but the other is a non-stall state. In the process of flow development, the evolution of low-frequency pressure fluctuation shows an obviousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The detailed simulation schemes and boundary conditions can be found in Kuang et al 41 Here is a brief introduction. The finite volume method was used to discrete the governing equations, and the DSM model 42 was employed to calculate the internal flow.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The detailed simulation schemes and boundary conditions can be found in Kuang et al 41 Here is a brief introduction. The finite volume method was used to discrete the governing equations, and the DSM model 42 was employed to calculate the internal flow.…”
Section: Methodsmentioning
confidence: 99%
“…Kuang et al 41 obtained the pressure fluctuation in the impeller mid-height at the inlet impeller passage under transient condition. They found that pressure fluctuations include low and high-frequency components.…”
Section: Pressure Fluctuation In the Passage Inletmentioning
confidence: 99%
See 2 more Smart Citations
“…In these schemes, the y + on average in the runner and guide vanes is less than 5, which meets the calculation requirements. 2628 Scheme 5 is selected for numerical simulation.
Figure 3.Grid refinement research.
…”
Section: Numerical Model Of the Pump-turbinementioning
confidence: 99%